Distribution of size and condition factors of blue crab (Portunus pelagicus Linnaeus, 1758) in the waters of Madong Village, Tanjungpinang city - Oktary, Qory; Zahid, Ahmad; Susiana, Susiana (Sangia Research Media and Publishing, 2024)
Management of blue swimming crab resources requires information about the condition of the blue swimming crab to determine the size that can be caught. The aim of this research is to analyze the structure of carapace width, gonad maturity level, and condition factors of blue swimming crab in the waters of Kampung Madong, Tanjungpinang City. The sampling point uses a purposive sampling method. Data collection used the census method. Fishing equipment used 60 bento traps. The results showed that 149 blue swimming crab samples were caught, consisting of 60 males and 89 females. The distribution of carapace width sizes on average is 95 - 103 mm which dominates. The growth coefficient for male blue swimming crab is the b value of 1.47 and for females the b value is 1.57, the dominant TKG is TKG II. The condition factor value is in the slightly flat category.